The Effectiveness of the Fit Adventure Educational Game on Physical Fitness Content in Relation to Student Learning Outcomes - Alif Putra Pradana; Sapto Adi; Imam Hariadi (Athena: Physical Education and Sports Journal, 2026)
This study aims to analyze the effectiveness of the Fit Adventure game-based learning media on students’ learning outcomes in physical fitness. This study employs a quantitative approach using a pre-experimental design in the form of a one-group pretest–posttest design. The research subjects were 57 students in Grade X A and X B of Phase E at MA Miftahush Shibyan. The instrument used was a physical fitness knowledge test developed based on the Learning Outcomes (CP) for Physical Education (PE) in Phase E. Data were analyzed using descriptive and inferential statistics through normality tests and paired-sample t-tests. The results of the study indicate a significant improvement in student learning outcomes following the use of the Fit Adventure game-based learning media, with a significance level of < 0.05 in both classes. Descriptively, the percentage of student learning outcomes also showed a significant increase from before to after the intervention. Thus, the Fit Adventure game-based learning media is effective for use in Physical Education and Health (PE) instruction, particularly for physical fitness content, as it enhances student engagement and learning outcomes.